Reciprocal Teaching Instruction at State Islamic Senior High School (Man) 1 Banjarnegara,Banjarnegara Regency, Indonesia - bin Ismail, Ahmad Munsif; bin Suhadak, Saiful Adli; bin Radin Abdul Halim, Radin Muhd. Imaduddin; Faizah, Inarotul; Dewilna Helmi (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The phenomenon of low active involvement and weak conceptual understanding in students of grades XI-7 MAN 1 Banjarnegara in the subject of Geography became the main trigger for the implementation of this research. The problem is allegedly rooted in the application of conventional instructional methods that still dominate the classroom, thus limiting students' intellectual mobility. As a solution, this Classroom Action Research (PTK) was initiated to evaluate the extent to which the Reciprocal Teaching model is able to escalate the dynamics of activities as well as the achievement of student learning outcomes through a more participatory approach. In its implementation, this study takes two action cycles that integrate the four pillars of cognitive strategy, namely summarizing, question generating, clarifying, and predicting. In Cycle I, observations showed that student involvement was still held at a low to moderate level, with the classical completion rate only reaching 46.7%. Nevertheless, through deep reflection and strengthening collaboration in Cycle II, there was a significant spike in the intensity of interaction in the classroom. It was recorded that students' questioning activities increased drastically to the very high category (81%), which was directly proportional to the increase in learning completeness which reached 70%. This success confirms that the paradigm shift, in which students take on the role of